Re-emigrants’ children in primary school - functioning in the educational system of Great Britain and learning in Poland - Nowicka, Monika (Activation-innovation-inspiration in (glotto) didactics, 2022)
The article focuses on the issue of teaching children of returnees from the UK who continue their education in the Polish primary school (stage II). It compares the Polish education system with the UK education system, which is the most frequent destination of immigration to Poland. The conclusions from the comparison of educational systems are compared with the statements of re-emigrants' children collected during the interviews, which describe their educational experiences in Poland and abroad.